Inelova Z., Nesterova S., Erubaeva G., Sejtkadyr K., Zaparina E., Baubekova A., Galamova G.G. The heavy metals in Alhagi pseudalhagi, Artemisia terrae-albae, Ceratocarpus arenarius of Mangystau region: Acting Associate Professor, Candidate of Biological Sciences, e-mail: arina.Inelova@kaznu.kz 2Professor, Doctor of Biological Sciences, e-mail: nesterova.2012@mail.ru 3Acting Associate Professor, Candidate of Biological Sciences, e-mail: g.yerubayeva@turan-edu.kz 4laboratory assistant, e-mail: seitkadyrova@list.ru 5laboratory assistant, e-mail: he_len.kz@mail.ru 6Candidate of Biological Sciences, e-mail: Almagul.Baubekova@kaznu.kz 7graduate student, e-mail: ggallamova@mail.ru Al-Farabi Kazakh National University, Kazakhstan, Almaty (Eurasian Journal of Ecology, 2018)
The article presents the results of a study of heavy metals concentration(Pb, Cd, Zn, Cu, Mn, Co, Ni)in the following samples of dominant plants: Alhagi pseudalhagi, Artemisia terrae-albae, Ceratocarpusarenarius and soils collected in the Mangistau region in 3 points: № 1 point (Aktau, the farm «Bereke»),number 2 point (Fort-Shevchenko, agriculture ‘ Asem-Almaz «) and number 3 (of Zhanaozen, the farm«Nurken»). The determination of heavy metals was carried out by atomic absorption spectrometry. Theprocedure for performing measurements of the mass fraction of petroleum products in soil samples wascarried out on a Fluorat-02 liquid analyzer. It was found, the studied plants in the studied points havedifferent accumulative abilities: Artemisia terrae-albae revealed the best accumulative ability to storeheavy metals when as Ceratocarpus arenarius differs in that, in comparison with other plants that growtogether with them under the same environmental conditions, they accumulate the least heavy metals.In all areas studied the content of heavy metals in soil samples it is within the acceptable level. However,there is a general pattern of a slight excess of the permissible level of concentration in the range of 1.09– 1.72 to the maximum permissible concentrations (MPC) for metals such as zinc, cobalt, which may berelated features physiographic zones and geological factors.Key words: Mangistau region, heavy metals, atomic absorption spectrometry, the dominant species,accumulative capacity